Changes in soil biological properties in different management and tyllage systems in petrocalcic argiudoll - Moreno, Maria Virginia (2020)
We analyzed the effect of different tillage systems on soils under different land-use histories, on biological properties of soil during one year. The experiment was carried out at a Petrocalcic Argiudoll of Tres Arroyos (Buenos Aires, Argentina). The specific aim was to describe and compare the soil organic carbon (SOC), the soil basal respiration (BR) and the activities of the enzyme dehydrogenase, urease and acid-phosphomonoesterase under zero and conventional tillage on soils under pasture and intensive agriculture. The SOC concentration was highest in summer (postharvest) independently of tillage system or land-use history. However, in autumn the plots under conventional tillage showed higher values of SOC than those with zero tillage, independently of land-use history. The BR had a significant benefit in favour of summer pasture soils. The effect of land-use history or the tillage system on the enzymes activity was dependent of sampling season. Therefore, the soil enzymes were more sensible than SOC and BR. In temporal studies the effect of sampling season is strongest that others factors as tillage systems or land-use history.